The Fwe of the Eastern Caprivi Zipfel : a study of their historical and geographical background, tribal structure and legal system, with special reference to Fwe family law and succession - Pretorius, Johan L. (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MA (Development Admin.))--University of Stellenbosch, 1975.